A preliminary examination of organizational faultlines in a biosafety context - Sargent, Moana (My University, 2026)
Organizational faultlines, or hypothetical dividing lines that split groups into subgroups (Lau & Murnighan, 1998), pose a unique threat to organizations in that they can lead to conflict, decreased performance, influence team sense-making processes, and sometimes team dissolution (Lau & Murnighan, 1998). Faultline research has largely focused on demographic faultlines (Thatcher & Patel, 2012). However, according to Social Identity Theory (Tajfel & Turner, 1986), faultlines may also form based on non-demographic characteristics. The current study aims to serve as a preliminary examination of non-demographic faultlines in high-risk, biosafety facilities with a novel approach to faultline measurement, advocating finite mixture modeling approaches, specifically latent profile analysis (LPA), for identifying underlying profiles in existing data in contexts where prevention is vital. This study measured non-demographic faultlines and group outcomes based on employees’ self-reports in a large biosafety facility. It was hypothesized that LPA would be an appropriate method to identify dormant faultlines and statistically significant differences between subgroups, that subgroups would be distinct, but have high within-group agreement, that faultlines would influence measurement invariance such that it was not achieved due to impact on sense-making, and that groups with high alignment would have high scores on group outcomes. Results support the use of LPA to identify dormant faultlines, that groups are homogenous and distinct from others, and that highly aligned groups had greater group outcomes. However, results did not indicate that faultlines influence measurement invariance. Implications include that LPA is an appropriate measurement method, especially in contexts where prevention is important, that highly aligned groups should have better outcomes, and that observed group differences may not be not due to measurement effects.
Keywords: Organizational faultlines; LPA; Biosafety; Subgroups